核桃油加工及抗氧化技术研究进展Research progress on walnut oil processing and antioxidant technology - 徐影影1,2，苗永军3，赵文革4，杜建4，郑畅1，刘昌盛1，陈洪建5，邓乾春1 XU Yingying1,2 , MIAO Yongjun3, ZHAO Wenge4, DU Jian4, ZHENG Chang1, LIU Changsheng1, CHEN Hongjian5, DENG Qianchun1 (Zhongguo youzhi)
核桃油营养丰富，富含不饱和脂肪酸及多种对人体有益的微量营养物质，但其稳定性差，在加工时易氧化酸败，极大地影响了核桃油产品的品质与安全，制约了核桃油产业的发展。为了改善核桃油品质，延长其货架期，重点综述了近年来有关核桃油加工技术对其氧化稳定性的影响和核桃油抗氧化技术的研究进展。核桃油加工技术主要包括前处理、提取和精炼，适宜的加工工艺有利于提高核桃油品质、保留微量营养成分及提高氧化稳定性。在抗氧化方面，可以采用添加抗氧化剂、制备调和油、将其制成微胶囊和油凝胶等延缓核桃油的氧化酸败。未来仍需探索合适的核桃油加工及抗氧化技术，以延长其货架期。Walnut oil is rich in nutrients, containing unsaturated fatty acids and a variety of beneficial trace nutrients for the human body. However, walnut oil has poor stability and is prone to oxidative rancidity during processing, which greatly affects the quality and safety of walnut oil products and constrains the development of the walnut oil industry. To improve the quality of walnut oil and extend its shelf life,the research progress in recent years on the impact of walnut oil processing technologies on its oxidative stability and the development of antioxidant technologies for walnut oil were reviewed. Walnut oil processing technologies mainly include pretreatment, extraction and refining. Appropriate processing technologies are beneficial for enhancing the quality of walnut oil, retaining trace nutrients, and improving oxidative stability. In terms of antioxidation, methods such as adding antioxidants, preparing blended oils, and forming microcapsules and oleogels can be used to delay the oxidative rancidity of walnut oil.There is still a need to explore suitable processing and antioxidant technologies to extend the shelf life of walnut oil in the future.